“You do it to cover your own back”: The assessment of cervical spine radiculopathy among physiotherapists in the United Kingdom: A mixed methods research study - Michael Mansfield; Stephanie T. Jong; Toby Smith (PLoS ONE, 2025)
Cervical spine radiculopathy [CSR] is a complex condition that is challenging to diagnose. The assessment methods used by United Kingdom [UK] physiotherapists to diagnose CSR remain unclear. A mixed-methods explanatory sequential design was used to investigate the assessment strategies that UK Health and Care Professions Council HCPC physiotherapists use and the reasons behind this decision-making in clinical practice. Phase 1 of the mixed methods research [MMR] study was a national online survey. The 63 respondents reported that the most common assessment strategies included muscle strength [94%], light touch sensation [78%] and reflex testing [89%]. Phase 2 of the MMR study included 11 qualitative interviews with Phase 1 [survey] participants. Four themes were established: perception of role, service constraints, minimising risk, and understanding symptoms. Physiotherapists often explained decision making in practice is based upon individual and organisational barriers. The choices available to physiotherapists may be based on cost, departmental knowledge and skill or convenience. However, the best available evidence suggests that physiotherapists should continue to use a biopsychosocial approach when establishing a CSR diagnosis. Physiotherapists should continue to embrace all assessment strategies available and strive to enhance or change practice.